Examining norms and social expectations surrounding exclusive breastfeeding: Evidence from Mali. (May 2022) - Bicchieri, Cristina; Das, Upasak; Gant, Samuel; Sander, Rachel
Highlights: We examine the implication of social expectations about community behavior and beliefs on individual exclusive breastfeeding behavior. We use primary survey data conducted in 2019 from 925 mothers of children of age two years or below from the Kayes and Sikasso regions in Mali. Perception about the prevalence and approval of exclusive breastfeeding within the community predict individual breastfeeding behavior. Analysis using random vignettes where levels of social expectations are experimentally manipulated indicates a potential causal link. Designing policy interventions that aim at altering social expectations can increase the prevalence of exclusive breastfeeding among mothers. Abstract: Do mothers' perceptions of community behavior and their beliefs about exclusive breastfeeding affect their own infant feeding behavior? We explore this relationship using a primary survey of 925 mothers with children of two years or below conducted in 2019 in the Kayes and Sikasso regions of Mali. Among other information, we collected self-reported data on the respondent's social expectations about the beliefs and behaviors of their community members apart from their own infant feeding behavior. The findings from regression estimations, after controlling for a host of potential confounding factors, indicate that children whose mothers think most individuals in her community exclusively breastfeed their infants, regardless of factual accuracy, are significantly more likely to be exclusively breastfed in the first six months. Beliefs about community approval of exclusive infant breastfeeding behavior are also found to be significantly associated, albeit modestly. In addition, children of mothers who hold false but positive beliefs and over-predict the prevalence of exclusive breastfeeding practices in the community are more likely to be exclusively breastfed. Further, we utilize responses from hypothetical vignettes where the levels of social expectations are experimentally manipulated. Here, prevalence of and beliefs about community infant feeding behavior are randomized across the respondents and then they are asked to predict the breastfeeding behavior of an imaginary vignette character under such conditions. The findings indicate a positive and robust relationship between the prevalence of community level exclusive breastfeeding and the predicted behavior concerning exclusive breastfeeding. A number of additional tests are conducted to ensure that the estimates are not confounded by unobserved heterogeneity. We assert that our findings can potentially represent an important foundation for the design of interventions aimed at altering social expectations, and thus effecting a measurable change in infant breastfeeding behaviors.